Estratégias dialógicas de construção de sentidos em aulas de leituras - Souza, Ramísio Vieira de (2017)
The approach of reading in the dialogical perspective of language is indispensable to the teaching of Portuguese language, as it enables the practice of reading according to this perspective and, consequently, the production of meanings through interactive relations between reader / author / text in the classroom. In this proposal, we argue that the reading strategies of the teacher are essential in the process of understanding, interpretation and meaning making of discursive genres. The goal is to understand the reading strategies used by the teacher in the process of reading the short story and chronicle genres in 9th grade classes. This research is qualitative and interpretative in nature and describes, interprets and analyzes selected data for this purpose. The corpus consists of four reading classes, totaling eighty-one minutes of recording, two from the state school teacher and two from the municipal school teacher. The rationale is mainly based on Bakhtin and the Circle and other authors who reflected on the Bakhtinian perspective, especially Almeida (2004; 2008; 2013; 2015). The results present the main strategies used by teachers: interactive, additive, explanatory, provocative questions / answers, indirect questions, resumption and exemplification. All of them are motivated by the voices of the readers when reading in the classroom, and among them, teacher / student, student / student, student / text, teacher / text that articulate to form the active responsive understanding of the student. In addition, they also show that the word is the bridge of interactive relationships between interlocutors, because it is a social sign capable of conveying values and ideologies in verbal interactions of language use. In interpretation, we find that there is no fixed place of meaning, because it is not ready in the student, teacher or text, but in the dialogical relations assumed by the subjects of learning in school. In the reading classes of P. (A), the emphasis was on the thematic content of the chronic genre, which provided the emergence of possible readings between teacher / student / text and the effects of meaning are real and significant. On the other hand, P. (B), who read the tale, had no productive effects on the construction of the meaning of the whole text, that is, the readings allowed by the context, purpose, theme and socio-historical conditions were not. considered during the interpretation of the genre. This factor is the result of the traditional conception of reading, predominant in their classes, which prioritizes the construction of the student's vocabulary and linguistic aspects over the comprehension of the tale. However, we evaluated as positive the reflection on the compositional structure of the short story, because the students identified some characteristics that compose it and identify it as this and not another genre. From the analysis, we affirm that the meaning does not have a fixed place and that the reading strategies of the teacher are essential to the teaching of reading at school, since it provides the formation of bundles of meaning that are the result of the responsive comprehension process of the student and consequently of meaning making of the text.